A study on ⟨(Q, S, R)-γ⟩-dissipative synchronisation of coupled reaction–diffusion neural networks with time-varying delays. Issue 4 (12th March 2018) - Ali, M. Syed; Zhu, Quanxin; Pavithra, S.; Gunasekaran, N.
ABSTRACT: This study examines the problem of dissipative synchronisation of coupled reaction–diffusion neural networks with time-varying delays. This paper proposes a complex dynamical network consisting of N linearly and diffusively coupled identical reaction–diffusion neural networks. By constructing a suitable Lyapunov–Krasovskii functional (LKF), utilisation of Jensen's inequality and reciprocally convex combination (RCC) approach, strictly〈 ( Q, S, R ) - γ 〉 -dissipative conditions of the addressed systems are derived. Finally, a numerical example is given to show the effectiveness of the theoretical results.